Sulfur positive electrode, all-solid-state lithium-sulfur battery and preparation method thereof
By using a sulfur positive electrode covered with an active lithium film and a lithium-free negative electrode in a lithium-sulfur battery, combined with a solid electrolyte, the problem of short cycle life of lithium-sulfur batteries is solved, and higher battery safety and energy density are achieved.
Patent Information
- Application Number
- CN202310988166.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-08
- Publication Date
- 2025-02-18
AI Technical Summary
The existing lithium-sulfur batteries have short cycle life due to the use of metal lithium negative electrodes, and the polysulfur ions shuttle of the sulfur positive electrode under the liquid lithium-sulfur system leads to rapid battery capacity loss.
A fully solid lithium-sulfur battery is used, and does not use a metal lithium negative electrode, but provides a lithium source through a sulfur positive electrode covered with an active lithium film. A stable lithium-free negative electrode is used, and a solid electrolyte is combined to extend the cycle life of the battery.
It has achieved the safety hazards of metal lithium negative electrodes, extended the service life of the negative electrodes, improved the cycle life of lithium sulfur batteries, and improved the safety reliability and energy density of the battery through solid electrolytes.
Smart Images

Figure CN119480881A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of batteries, and in particular relates to an all-solid-state lithium-sulfur battery. Background Art
[0002] With the rapid development of lithium batteries, the energy density of lithium-ion batteries has approached its theoretical value, and it is urgent to develop the next generation of high energy density battery systems. Lithium-sulfur batteries have always been a hot topic of research due to their high energy density (up to 500Wh / kg or more).
[0003] Normally, there is no active lithium in the positive electrode of lithium-sulfur batteries, so metallic lithium is generally used as the negative electrode. Since metallic lithium is soft and unsupported, the thickness of lithium strips needs to be increased to achieve battery assembly, and the amount used will be more than the actual demand. In addition, a series of problems with metallic lithium negative electrodes (dendrites, volume expansion, etc.) can also lead to the failure of metallic lithium negative electrodes and short battery cycle life.
[0004] In addition to the influence of the metallic lithium negative electrode, in the liquid lithium-sulfur system, the polysulfide ions produced by the sulfur positive electrode shuttle between the positive and negative electrodes, which will also cause rapid loss of battery capacity and a decrease in the battery cycle life.
[0005] In summary, it is indeed necessary to provide an all-solid-state lithium-sulfur battery that avoids the use of metallic lithium negative electrode and has a long cycle life. Summary of the invention
[0006] The present invention provides an all-solid-state lithium-sulfur battery, which does not use a metallic lithium negative electrode, but instead provides a lithium source through a sulfur positive electrode covered with an active lithium film to achieve battery circulation; in addition, the lithium-sulfur battery uses a stable lithium-free negative electrode, which can greatly extend the service life of the negative electrode, thereby improving the cycle life of the lithium-sulfur battery.
[0007] The sulfur positive electrode of the all-solid-state lithium-sulfur battery of the present invention contains a solid electrolyte as a lithium ion transmission medium, wherein the active lithium film reacts with the active sulfur under the action of the primary battery. Since the active sulfur is adsorbed in the carbonaceous carrier material with a very large specific surface area, the lithium ions are uniformly combined with the active sulfur to form polysulfides; by controlling the amount of active lithium used and the formation process of the all-solid-state lithium-sulfur battery, the controllable generation of short-chain polysulfides can be achieved.
[0008] In order to achieve the above objectives, in a first aspect, the present invention provides a sulfur positive electrode, comprising a sulfur positive electrode membrane and an active lithium film covering the sulfur positive electrode membrane, wherein the sulfur positive electrode membrane contains active sulfur, a carbonaceous carrier skeleton, and a solid electrolyte, and their mass ratio in the membrane is (5-35): (10-20): (55-75), wherein the active sulfur is adsorbed on the surface of the carbonaceous carrier skeleton, and the solid electrolyte is filled between the carbonaceous carrier skeletons adsorbed with active sulfur; the mass of active lithium in the active lithium membrane is 10%-45% of the mass of the active sulfur.
[0009] In some embodiments, the active sulfur in the sulfur positive electrode membrane is elemental sulfur, sulfurized polyacrylonitrile and a combination thereof.
[0010] In some embodiments, the carbonaceous carrier skeleton in the sulfur positive electrode membrane includes a surface-treated carbonaceous carrier material, and the carbonaceous carrier material is carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbide and a combination thereof, and the material surface of the surface-treated carbonaceous carrier material has at least one of the following chemical bonds: CN, CO, CB, CP, CS, CM (M is a metal element, including at least one of Li, Na, Mg, Al, Fe, Ti, K, Ca, Cr, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ag, In, Sn, Au, Pt, W, Pb, Ge), CF, C-Cl, C-Br, CI.
[0011] In some embodiments, the solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte, or an organic-inorganic composite solid electrolyte.
[0012] In some embodiments, the active lithium film is a metallic lithium film having a thickness of 1 micrometer to 50 micrometers.
[0013] In some embodiments, the metallic lithium film has through pores, and a porosity of 1% to 85%.
[0014] In a second aspect, the present invention provides an all-solid-state lithium-sulfur battery, comprising the above-mentioned sulfur positive electrode, a lithium-free negative electrode and a solid electrolyte, wherein the active lithium in the active lithium film reacts with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.
[0015] In some embodiments, the sulfur cathode film includes a surface-treated carbonaceous carrier material, the Li2S x adsorbed on the carbonaceous support material.
[0016] In some embodiments, the lithium-free negative electrode includes a graphite negative electrode, a silicon-carbon negative electrode, or a silicon-oxygen negative electrode.
[0017] In some embodiments, the solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte, or an organic-inorganic composite solid electrolyte. The solid electrolyte here may be the same as or different from the solid electrolyte contained in the sulfur positive electrode membrane.
[0018] In a third aspect, the present invention provides a method for preparing the above-mentioned all-solid-state lithium-sulfur battery, comprising:
[0019] Step 1, preparing a mixture of a sulfur positive electrode active material (active sulfur) and a surface-treated carbonaceous carrier material;
[0020] Step 2, uniformly mixing the above mixture with solid electrolyte powder and a binder;
[0021] Step 3, loading the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur-containing positive electrode membrane;
[0022] Step 4, loading the active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium;
[0023] Step 5: Assemble the sulfur positive electrode covered with active lithium, the lithium-free negative electrode, the solid electrolyte and the packaging materials into an all-solid-state lithium-sulfur battery.
[0024] In some embodiments, the active lithium film in step 4 is supported on the sulfur cathode film by at least one method selected from the group consisting of coating, rolling, physical vapor deposition, and magnetron sputtering.
[0025] In some embodiments, the method further comprises reacting the active lithium in the active lithium film with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.
[0026] In some embodiments, the formation step may be performed at a constant voltage until the current is less than 0.005C.
[0027] In some embodiments, the surface-treated carbonaceous carrier material described in step 1 is prepared by any one of the following methods: surface defect treatment of carbonaceous material, mainly using high-temperature chemical corrosion to connect impurity atoms to the surface of the carbonaceous carrier material, such as sintering the carbonaceous carrier material at high temperature, using nitrogen as a protective gas, and forming CN bonds at the defect positions of the carbonaceous carrier material. In addition to gas, solid substances can also be mixed with carbonaceous carrier materials and then sintered at high temperature, such as sodium carbonate reacting with carbon to form C-Na bonds.
[0028] In some embodiments, in step 1, the spheroidal graphite is mixed and then treated at a high temperature of 120° C. to 200° C. for 1-5 hours in a tube furnace under atmosphere protection, so that active sulfur is adsorbed on the surface of the carbonaceous carrier material.
[0029] The all-solid-state lithium-sulfur battery of the present invention has at least the following advantages:
[0030] 1. The lithium-sulfur battery of the present invention avoids using metallic lithium as the negative electrode in the lithium-sulfur battery, thereby avoiding the potential safety hazards caused by metallic lithium during use; a variety of lithium-free materials or foil materials can be used as the negative electrode, the negative electrode is relatively stable and reliable relative to metallic lithium, and the battery cycle life is long.
[0031] 2. Active lithium and active sulfur in the sulfur positive electrode form short-chain polysulfide Li2S x , x is less than or equal to 4, this short-chain polysulfide can be easily adsorbed on the carbonaceous carrier material, and the heterogeneous atoms (including N, O, B, P, S, metal atoms, etc.) on the surface of the carbonaceous material provide affinity sites for the short-chain polysulfide molecules. Through the action of chemical bonds, the short-chain polysulfide on the surface of the carbonaceous carrier material can not only prevent the "sulfur shuttling" problem of lithium polysulfide, but also solve the problem of poor conductivity of active sulfur in the sulfide positive electrode and few active sites for reaction with metallic lithium.
[0032] 3. In the all-solid-state lithium-sulfur battery, the all-solid-state electrolyte in the sulfur positive electrode not only acts as a lithium ion transmission medium but also wraps the carbonaceous carrier skeleton, thereby binding (solidifying) the active sulfur on the surface of the carbonaceous carrier skeleton and avoiding / reducing the "sulfur shuttling" problem.
[0033] 4. The all-solid-state lithium-sulfur battery uses solid electrolyte instead of conventional liquid electrolyte. The battery is safe and reliable and has high energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 A schematic diagram of the sulfur cathode structure of the present invention;
[0035] Figure 2 The cycle number and discharge capacity curves of the assembled batteries of Example 1 and Comparative Example 1.
[0036] Description of reference numerals:
[0037] 1 Current collector 2 Active lithium film 3 Solid electrolyte 4 Surface treated carbonaceous carrier material 5 Active sulfur DETAILED DESCRIPTION
[0038] The content of the present invention will be described below in conjunction with the accompanying drawings. For the purpose of clear description, many details will be described together in the following description. However, it should be understood that these details should not be used to limit the present invention. In addition, to simplify the drawings, some known conventional structures and elements will be illustrated in a simple schematic manner in the drawings. The "about", "approximately" or "roughly" used herein is used to modify any slightly variable quantity, but this slight change does not change its essence. If not otherwise specified, the error range of the modified numerical value represented by "about", "approximately" or "roughly" is generally within the allowable range, preferably within 10%, and more preferably within 5%.
[0039] The structural schematic diagram of a sulfur positive electrode of the present invention is as follows Figure 1 shown.
[0040] The sulfur positive electrode of the present invention includes a sulfur positive electrode membrane, which is formed on a current collector 1 and covered with an active lithium film 2, wherein the sulfur positive electrode membrane comprises a solid electrolyte 3, a surface-treated carbonaceous carrier skeleton 4 and active sulfur 5, wherein the active sulfur 5 is adsorbed on the surface of the carbonaceous carrier skeleton 4, and the solid electrolyte 3 is filled between the carbonaceous carrier skeletons adsorbed with active sulfur. The sulfur positive electrode membrane can be formed on both sides of the current collector 1 (such as Figure 1 As shown), it can also be formed on only one side.
[0041] In the sulfur positive electrode of the present invention, the mass of active lithium is 10%-45% of the mass of active sulfur. The active material in the sulfur positive electrode is elemental sulfur, sulfide polyacrylonitrile and their combination. Active lithium can form Li2Sx with active sulfur in the sulfide positive electrode, wherein the value of x is less than or equal to 4, and this short-chain polysulfide can be easily adsorbed on a carbonaceous carrier material with a large specific surface area, and these carbonaceous carrier materials include but are not limited to carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbides and their combination. The heterogeneous atoms (including N, O, B, P, S, metal atoms, etc.) on the surface of the carbonaceous material provide affinity sites for short-chain polysulfide molecules. Through the action of chemical bonds, the short-chain polysulfide on the surface of the carbonaceous carrier material can solve the problem of poor conductivity of active sulfur in the sulfide positive electrode and few active sites for reaction with metallic lithium, and these heterogeneous atoms can also catalyze the lithium-sulfur reaction and promote the generation of short-chain lithium polysulfide. In addition, a large amount of solid electrolytes can conduct lithium ions to complete the solid-phase reaction process of lithium polysulfide, and can also wrap the sulfur positive electrode to prevent the "sulfur shuttling" of lithium polysulfide.
[0042] Usually, lithium-sulfur batteries are matched with metal lithium negative electrodes, but the lithium-sulfur battery of the present invention avoids using metal lithium negative electrodes, and instead uses lithium-free negative electrodes, including graphite negative electrodes, silicon-carbon negative electrodes, and silicon-oxygen negative electrodes. These negative electrodes are more stable than metal lithium negative electrodes, and will not form lithium dendrites. The service life of the negative electrode is no longer a shortcoming that limits the service life of lithium-sulfur batteries.
[0043] The lithium-sulfur battery prepared by combining the above-mentioned sulfur positive electrode covered with an active lithium film with a lithium-free negative electrode with stable performance has a cycle life that is significantly better than the traditional lithium-sulfur battery using a metallic lithium negative electrode.
[0044] During the preparation of the sulfur positive electrode, an active lithium film with a thickness of 1 to 50 microns is coated on the surface of the sulfur positive electrode. The thickness of the active lithium film is selected according to the mass of active sulfur in the sulfur positive electrode, which can effectively control the overall molecular weight of polysulfides in the sulfur positive electrode.
[0045] The sulfur positive electrode and lithium-free negative electrode of the all-solid-state lithium-sulfur battery of the present invention are compatible with various solid electrolytes, wherein the solid electrolyte can be selected from at least one of a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte, and an organic-inorganic composite solid electrolyte.
[0046] Sulfide solid electrolytes include: Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 12 , Li6PS5Cl, 0.7Li2S–0.3P2S5, β-Li3PS4, etc.; oxide solid electrolytes include: Li 0.34 La 0.51 TiO 2.94 , Li 0.38 La 0.56 Ti 0.99 Al 0.01 O3, LiTi2(PO4)3, Li 1.2 Al 0.2 Ti 1.8 (PO4)3、Li 0.34 Nd 0.55 TiO3, etc.
[0047] Organic solid electrolytes include: polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polymethyl acrylate, etc.
[0048] The organic-inorganic composite solid electrolyte includes: a combination of the above-mentioned organic solid electrolyte and a sulfide solid electrolyte and an oxide solid electrolyte.
[0049] The preparation method of the all-solid-state lithium-sulfur battery of the present invention is simple, and the preparation method comprises the following steps:
[0050] Step 1, preparing a mixture of sulfur positive electrode active material (activated sulfur) and carbonaceous carrier material;
[0051] Step 2, uniformly mixing the above mixture with solid electrolyte powder and a binder;
[0052] Step 3, loading the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur positive electrode membrane;
[0053] Step 4, loading the active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium;
[0054] Step 5: Assemble the sulfur positive electrode covered with active lithium with the lithium-free negative electrode, solid electrolyte and packaging materials to prepare an all-solid-state lithium-sulfur battery.
[0055] Wherein, the active lithium film described in step 4 is loaded on the sulfide positive electrode film by at least one method of coating, rolling, physical vapor deposition, and magnetron sputtering.
[0056] In addition, the preparation method of the present invention further comprises reacting the active lithium in the active lithium film with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.
[0057] The specific conditions of the battery formation process include: constant voltage charging, constant voltage at 2.05V, current cutoff, and formation is completed after the current is less than 0.005C.
[0058] Example 1
[0059] Preparation of sulfur cathode covered with active lithium film
[0060] The carbon nanotubes were placed in a tubular furnace, nitrogen was introduced as a protective atmosphere, and the carbon nanotubes were treated at 800°C.
[0061] Elemental sulfur (Aladdin) and surface treated carbon nanotubes (Shandong Dazhan) were uniformly mixed in a ball mill at a mass ratio of 3:5 for 24 hours and treated at 150°C for 2 hours. After mixing, sulfide solid electrolyte (Li 10 GeP2S 12 Cl, Shenzhen Kejing) and binder polyethylene terephthalate (without using solvent), and subjected to fiberization treatment at 150 °C, extruded onto stainless steel foil and rolled to prepare sulfur positive electrode membrane.
[0062] A 5-micron-thick active lithium film (Tianjin Zhongneng Lithium Industry Co., Ltd.) was attached to the surface of the above-mentioned sulfur positive electrode membrane, and a pressure of 3MPa was applied for compaction treatment. The compaction treatment time was 4 hours at a temperature of 45°C, and finally a sulfur positive electrode covered with an active lithium film was obtained.
[0063] Preparation of graphite anode
[0064] The graphite negative electrode, the binder, and the conductive agent were dispersed in deionized water at a mass ratio of 95:2:3, homogenized, coated, and dried to prepare a graphite negative electrode with a thickness of 50 microns.
[0065] The sulfur positive electrode covered with the active lithium film and the graphite negative electrode were separated by a sulfide solid electrolyte, and the soft pack battery was assembled by Z-shaped lamination process, and the all-solid-state lithium-sulfur battery was assembled under a pressure of 60MPa. After the assembled full battery was formed, the charge and discharge cycle test was carried out. The test procedure was as follows: charging with a current of 5mAh, the cut-off voltage was 3V, and then discharging with a current of 5mAh, the discharge cut-off voltage was 1.7V, and the number of cycles and the discharge capacity of the battery were recorded.
[0066] Example 2
[0067] Specific implementation method The same as in Example 1, except that an oxide solid electrolyte sheet (Shenzhen Kejing) is used.
[0068] Example 3
[0069] Specific implementation method As in Example 1, only the composite solid electrolyte prepared by composite of polyethylene oxide (average molecular weight 1 million) and oxide solid electrolyte powder (Shenzhen Kejing) is changed.
[0070] Comparative Example 1
[0071] Specific implementation method As in Example 1, only the graphite negative electrode is changed to a pure metal lithium foil with a thickness of 50 microns (Tianjin Zhongneng Lithium Industry Co., Ltd.).
[0072] Figure 2 The cycle number and discharge capacity curves of the assembled batteries of Example 1 and Comparative Example 1. As can be seen from the figure, the discharge capacity of the all-solid-state lithium-sulfur battery of Comparative Example 1 is slightly higher than that of the battery of Example 1, but the discharge capacity of the all-solid-state lithium-sulfur battery of Comparative Example 1 begins to decay rapidly after 50 cycles. This is because the volume of the metal lithium negative electrode changes seriously during the cycle, resulting in a large amount of "dead lithium", which in turn rapidly reduces the active lithium of the entire battery and causes the discharge capacity to decay. The battery cycle life of Example 1 using a lithium-free negative electrode is significantly extended. When the cycle reaches about 85 weeks, the battery discharge capacity begins to decay rapidly.
[0073] Obviously, those skilled in the art can make various changes and modifications to the present disclosure without departing from the spirit and scope of the present disclosure. Thus, if these modifications and variations of the present disclosure fall within the scope of the claims of the present invention and their equivalents, the present disclosure is also intended to include these modifications and variations.
Claims
1. A sulfur cathode, characterized in that: The sulfur positive electrode comprises a sulfur positive electrode membrane and an active lithium film covering the sulfur positive electrode membrane, wherein: The sulfur positive electrode membrane comprises active sulfur, a carbonaceous carrier skeleton and a solid electrolyte, wherein the mass ratio of the active sulfur to the carbonaceous carrier skeleton is (5-35): (10-20): (55-75), wherein the active sulfur is adsorbed on the surface of the carbonaceous carrier skeleton, and the solid electrolyte is filled between the carbonaceous carrier skeletons adsorbed with the active sulfur; The mass of active lithium in the active lithium film is 10%-45% of the mass of active sulfur.
2. The sulfur cathode according to claim 1, characterized in that The active sulfur in the sulfur positive electrode membrane is elemental sulfur, sulfurized polyacrylonitrile and a combination thereof.
3. The sulfur cathode according to claim 1, characterized in that The carbonaceous carrier skeleton is carbon nanotubes, graphene, ordered mesoporous carbon, transition metal carbide and combinations thereof. Preferably, the carbonaceous carrier skeleton is surface-treated to have at least one of the following chemical bonds on the surface: CN, CO, CB, CP, CS, CM (M is a metal element, including at least one of Li, Na, Mg, Al, Fe, Ti, K, Ca, Cr, Mn, Co, Ni, Cu, Zn, Zr, Mo, Ag, In, Sn, Au, Pt, W, Pb, Ge), CF, C-Cl, C-Br, CI; The solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte or an organic-inorganic composite solid electrolyte.
4. The sulfur cathode according to claim 1, characterized in that The active lithium film is a metallic lithium film, and its thickness is 1 micron to 50 microns; Preferably, the metal lithium film has through holes, and a porosity of 1% to 85%.
5. An all-solid-state lithium-sulfur battery, characterized in that: The lithium-sulfur battery comprises: The sulfur cathode according to any one of claims 1 to 4; No lithium anode; and Solid electrolytes, Among them, the active lithium in the active lithium film reacts with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.
6. The all-solid-state lithium-sulfur battery according to claim 5, characterized in that: The Li2S x Adsorbed on the carbonaceous carrier skeleton.
7. The all-solid-state lithium-sulfur battery according to claim 5, characterized in that: The lithium-free negative electrode includes a graphite negative electrode, a silicon-carbon negative electrode or a silicon-oxygen negative electrode.
8. The all-solid-state lithium-sulfur battery according to claim 5, characterized in that: The solid electrolyte includes a sulfide solid electrolyte, an oxide solid electrolyte, an organic solid electrolyte or an organic-inorganic composite solid electrolyte.
9. A method for preparing an all-solid-state lithium-sulfur battery as claimed in any one of claims 5 to 8, comprising: Step 1, preparing a mixture of a sulfur cathode active material (activated sulfur) and a carbonaceous carrier skeleton; Step 2, uniformly mixing the above mixture with solid electrolyte powder and a binder; Step 3, curing the mixture obtained in step 2 on the surface of the current collector to obtain a sulfur positive electrode membrane; Step 4, loading an active lithium film on the sulfur positive electrode film to obtain a sulfur positive electrode covered with active lithium; Step 5: Assemble the sulfur positive electrode covered with active lithium, the lithium-free negative electrode, the solid electrolyte and the packaging materials into an all-solid-state lithium-sulfur battery.
10. The method according to claim 9, characterized in that The method further comprises reacting the active lithium in the active lithium film with the active sulfur in the sulfur positive electrode film to form Li2S x , where x is less than or equal to 4.
Citation Information
Cited By
Thick electrode for lithium-sulfur battery and preparation method of thick electrode
CN120413599A
Composite positive electrode for solid-state lithium-sulfur battery and preparation method of composite positive electrode
CN120955081A
A composite cathode for solid-state lithium-sulfur batteries and a method of making the same
CN120955081B